UMP-China connection - UMP, PNC (Pejabat Naib Canselor, 2009)
In line with the University’s Strategic Planning, a delegation from Universiti Malaysia Pahang (UMP) headed by the Vice-Chancellor, Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim visited China from 17th - 23rd March recently.